The Theory of Magnitudes - Weinstock, Daniel (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
This is a way to look at a photos of stars and make sense to get a value that shows the closest star: in the vicinity: It uses star’s apparent magnitudes to get theses inverse magnitudes and to get a nearby star of the largest ratio ; of the inverse apparent magnitude divided by the distance. Now the beginning reference star obeys this ratio . For the greater the distance the lower the value. And we want the highest value . The greater the brightness enlarges and the greater the distance makes the value lessons. After trying to use aspects of General Relativity’s Tensor Calculus, l found l could not find my formulas to fit the data . In an original way l used the inverse Apparent Magnitudes in Astronomical to get a consistant formula that is data proven with general ideas from Global analysis. It works with Star charts/photos. Before l even tried using the inverse of the determinates of linear algebra. But my attempts were to no avail. Therefore l became inspired by basic formulas in General Relativity but that did not work. Using Global Analysis in an new l succeeded. Keywords Using my new formula l can obtain the distance between a reference star, using its inverse apparent magnitude, l obtain the distance to from another star using certain restrictions which the measurement in centimeters to this other star from its reference star nearby.